PERAN PENDIDIKAN MULTIKULTURAL DALAM MENCEGAH PERILAKU BULLYING DIKALANGAN SISWA SEKOLAH - Endayani, Henni (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2024)
Multicultural education is an educational program that aims to provide knowledge for students about differences that exist in society such as differences in language, ethnicity, skin color, language, religion, gender, culture, socio-economic status as a natural thing. So as to foster an attitude and behavior of mutual respect among students. This aims to prevent bullying that occurs in schools. Bullying is an act of violence that can cause suffering to the victim. Bullying can be divided into four types, namely physical, verbal, relational and cyber bullying. One of the goals of multicultural education is to prevent bullying behavior committed by students. This can be done by integrating multicultural education materials into the curriculum, which can be done with four approaches, namely: (1) Contribution approach and implementation of contribution approach in class (2) Additive approach and implementation of additive education in class (3) Transformation approach and implementation of transformative approach in class (4) Social action approach and implementation of social action approach in class.Keywords: Education, Multicultural, Bullying, School